How low-abundance amphibians shape functional diversity across tropical forest succession stages? - Fabio Zabala-Forero; Angela M. Cortés-Gómez; Nicolás Urbina-Cardona (Ecological Indicators)
The role of low-abundance species in ecosystems remains largely understudied, despite their unique trait values and significant influence on biotic interactions and ecosystem processes. Trait-based ecology provides key insights into the impact of these species on functional diversity metrics, particularly in landscapes undergoing ecological succession after land abandonment in tropical forests. This study evaluates the effects of sequentially losing low-abundance species on amphibian functional diversity in the Colombian Pacific region. We applied trait probability density (TPD) analysis at the assemblage level and functional rarity indices (Scarcity and Functional Distinctiveness) at the species level. By simulating scenarios of low-abundance species loss, we assessed changes in functional diversity metrics—such as richness, evenness, divergence, and redundancy—across three vegetation types: mature forest, secondary forest, and abandoned mixed crops. Our findings revealed significant variations in functional diversity metrics. Functional richness was sensitive to both vegetation types and species loss scenarios, while functional evenness and redundancy responded more specifically to the loss of low-abundance species. Correlation analyses showed significant relationships between species richness and functional diversity metrics. Interestingly, species with the highest Scarcity and Functional Distinctiveness values, which also had the lowest abundances, were the first to be lost in the scenarios. These results underscore the vital importance of low-abundance amphibian species in maintaining functional diversity and advocate for conservation strategies prioritizing these vulnerable species and their habitats. Our study revealed the intricate relationship between species richness and facets of functional diversity under scenarios of local extinction and anthropogenic land cover transitions in tropical ecosystems.